Optimisation Best Sales Assessment Using aCombination of Rank Order Centroid and Additive Ratio Asessment Algorithms - Yulvia Nora Marlim; Erlin; Susanti, Wilda; Jollyta, Deny; Oktarina, Dwi (INOVTEK Polbeng - Seri Informatika, 2024)
Employee assessment in a company is one of the tricks used to improve employee performance, so that it can be profitable for the company. One of the methods used to determine the best employees is to use a decision support system (DSS). By using DSS, decision making becomes faster, more accurate, efficient and effective. This study was used to determine the best sales at PT Surya Asia Abadi. By combining the Rank Order Centriod (ROC) Algorithm and Additive Ratio Assessment (ARAS) in the DSS, it can produce a better level of prediction accuracy and decision making based on the processed data. Where in this study using 6 (six) variables and 7 (seven) alternatives. The ROC algorithm is used to find the weight of each variable, and the weight obtained from the ROC is then processed using the ARAS algorithm to obtain alternative rankings. The purpose of this study is to make it easier for the Company to determine the best employees with more accurate results. The research results showed that the highest ranking was achieved by alternative AL3 with a value of 0.884 and the lowest was obtained by alternative AL1 with a value of 0.684.